Qualitative Aspects for Volterra Integro-Dynamic Matrix Sylvester Impulsive System on Time Scales - Sreenivasulu, A.; Rao, B. V. Appa (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we establish the asymptotic stability and boundedness of the Volterra integro-dynamic matrix Sylvester impulsive system on time scales. First, we convert the linear Volterra integro-dynamic matrix Sylvester impulsive system on time scale to an equivalent Kronecker product Volterra integro-dynamic impulsive system on time scales using vectorization operator. Then, we obtaine the results for asymptotic stability and boundedness of a time-varying Volterra integro-dynamic matrix Sylvester impulsive system on time scales in which the coefficient matrix is not necessarily stable. We generalize to a time scale some known properties concerning the asymptotic stability and boundedness from the continuous version. Finally, we've given some numerical and theoretical examples of the way those advanced analytical consequences may be applied.